Backyard Chicken Flocks Pose a Disease Risk for Neotropic Birds in Costa Rica - Hernandez Diver, Sonia (2008)
Pathogens of free-ranging chickens create a risk of disease for wild birds, some of which migrate to the United States, as well as potential economic losses for resource-poor farmers. Free-roaming backyard chickens are commonly kept in shade-grown coffee plantations, habitats that attract large numbers of wild birds. The husbandry and pathogen prevalence of backyard chicken flocks in San Luis, Costa Rica, were investigated. Based on serologic evidence, Newcastle disease virus, infectious laryngotracheitis virus, infectious bronchitis virus, chicken anemia virus, and infectious bursal disease virus, as well as both Mycoplasma gallisepticum and Mycoplasma synoviae, appear to be significant diseases of this population, and thus, we consider these backyard chickens potential reservoirs for these diseases. There was no evidence of avian influenza. Interviews, clinical examinations, and microscopic examination of tissues led us to believe that poxvirus is also a significant cause of morbidity and mortality in these chickens. We found that Escherichia coli isolates were resistant against tilmicosin, tetracycline, ampicillin, amoxicillin with clavulanic acid, ticarcillin, and cephalothin, and contained genes considered responsible for conferring tetracycline resistance. Additionally, although production was not measured, we suspect that husbandry and lack of preventative medicine are directly related to the diseases reported, all of which negatively affect production.